Simulation-Based Experiential Learning for Developing Professional Writing Competency: A Human Capital Perspective - Vega Fonsula Andromeda (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Writing is increasingly recognized as a critical employability skill and a core component of organizational communication. However, traditional instructional approaches often fail to connect technical knowledge with communication capabilities. This study examines the role of simulation-based experiential learning in enhancing professional writing competency within a management and training context. This study adopts a quasi-experimental design using a pretest–posttest approach involving 104 cadets from maritime institutions. The intervention integrates a navigation light simulator within an experiential learning framework to support the development of writing skills in Maritime English. The results indicate a statistically significant improvement in participants’ performance, supported by an increase in mean scores, a moderate effect size, and a normalized gain score of 0.33. Additionally, reduced score variability suggests improved competency alignment across participants. From a management perspective, these findings highlight the effectiveness of experiential, simulation-based training as a mechanism for human capital development, particularly in enhancing communication-intensive competencies. The study contributes to the literature by extending experiential learning theory into the domain of professional communication and employability. Practical implications suggest that integrating simulation-based learning into training design can bridge the gap between technical expertise and communication skills required in organizational settings.